2019
DOI: 10.32859/era.18.20.1-17
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal plant species used in the treatment of skin diseases in Katabi Subcounty, Wakiso District, Uganda

Abstract: Background: The use of medicinal plants in primary healthcare is central among rural communities in Uganda due to the expensive and often inaccessible conventional healthcare. Skin diseases pose a serious health risk given the challenge of HIV-AIDS whose opportunist infections manifest themselves as skin complications. The study investigated, identified and documented plant species used to manage skin infections, the plant parts used, methods of preparation and administration of herbal remedies.Methods: An eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
0
18
0
1
Order By: Relevance
“…27 It has a wide folkloric use against diverse diseases. More importantly, it has gained wide application in the management of wound, [28][29][30][31][32][33] and other medicinal uses such as relieve of headache, 34 antiplasmodial, [35][36][37][38][39] antibacterial, 34,40,41 diarrheal disease, [42][43][44][45] snake bite poison, [46][47][48][49] cataract, 40,50 toothache, 44 placenta removal, 33,51,52 skin cut/infection, [53][54][55] dermatitis, 56 febrile convulsion, 57 anti-trypanosomal, 33 endo/ ectoparasite, 58,59 cancer or tumour, 60 and eye infection and warts. 61 The volatile oil from the leaf, crude extracts, fractions, and isolated pure compounds were tested in vitro to evaluate antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…27 It has a wide folkloric use against diverse diseases. More importantly, it has gained wide application in the management of wound, [28][29][30][31][32][33] and other medicinal uses such as relieve of headache, 34 antiplasmodial, [35][36][37][38][39] antibacterial, 34,40,41 diarrheal disease, [42][43][44][45] snake bite poison, [46][47][48][49] cataract, 40,50 toothache, 44 placenta removal, 33,51,52 skin cut/infection, [53][54][55] dermatitis, 56 febrile convulsion, 57 anti-trypanosomal, 33 endo/ ectoparasite, 58,59 cancer or tumour, 60 and eye infection and warts. 61 The volatile oil from the leaf, crude extracts, fractions, and isolated pure compounds were tested in vitro to evaluate antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Two more studies from Mpigi district identified the stem bark and the leaves for treatment of HIV/AIDS and related medical disorders [ 17 , 58 ]. At another study site in Uganda, Katabi subcounty in Wakiso district, the leaves and the bark were used in treatment of wounds and skin rashes [ 97 ]. In Kakamega county, Kenya, the bark and the leaves were reported to be used in treatment of breast, uterine, and skin cancer [ 98 ].…”
Section: Resultsmentioning
confidence: 99%
“…People usually choose the herbal products instead of medical drugs [46]. The use of medical plant species in the treatment of children diseases is a part of traditional knowledge that is handed down by hearsay advices [20].…”
Section: Discussionmentioning
confidence: 99%
“…It is predicted that this rate will be greater for the COVID-19 pandemic process. WHO has been reported nearly ~80% of the world's population uses and trust herbal products for treatment [17][18][19][20].…”
Section: Prevalence Of Herbal Medicinal Product Usementioning
confidence: 99%